Expanding the expression 6(x + 1) involves distributing the 6 to both terms inside the parentheses.
6(x + 1) = 6 * x + 6 * 1
= 6x + 6
So, the expanded form of 6(x + 1) is 6x + 6.
Expand 6(x + 1) .(1 point)
13 answers
Expand 4(3z − 7).(1 point) $$
Expanding the expression 4(3z - 7) involves distributing the 4 to both terms inside the parentheses.
4(3z - 7) = 4 * 3z - 4 * 7
= 12z - 28
So, the expanded form of 4(3z - 7) is 12z - 28.
4(3z - 7) = 4 * 3z - 4 * 7
= 12z - 28
So, the expanded form of 4(3z - 7) is 12z - 28.
Expand −5(2q + 8).(1 point)
Expanding the expression -5(2q + 8) involves distributing the -5 to both terms inside the parentheses.
-5(2q + 8) = -5 * 2q - 5 * 8
= -10q - 40
So, the expanded form of -5(2q + 8) is -10q - 40.
-5(2q + 8) = -5 * 2q - 5 * 8
= -10q - 40
So, the expanded form of -5(2q + 8) is -10q - 40.
Expand 7/10(5d+6) .(1 point)
Expanding the expression (7/10)(5d + 6) involves distributing the 7/10 to both terms inside the parentheses.
(7/10)(5d + 6) = (7/10) * 5d + (7/10) * 6
= (7/10)(5d) + (7/10)(6)
= (7/10)(5d) + (7/10)(6/1) (dividing 6 by 1 to make it have the same denominator as 10)
= 35d/10 + 42/10
Next, we can simplify the expressions:
35d/10 + 42/10 = (35d + 42)/10
So, the expanded form of (7/10)(5d + 6) is (35d + 42)/10.
(7/10)(5d + 6) = (7/10) * 5d + (7/10) * 6
= (7/10)(5d) + (7/10)(6)
= (7/10)(5d) + (7/10)(6/1) (dividing 6 by 1 to make it have the same denominator as 10)
= 35d/10 + 42/10
Next, we can simplify the expressions:
35d/10 + 42/10 = (35d + 42)/10
So, the expanded form of (7/10)(5d + 6) is (35d + 42)/10.
use the order of operations to simplify (solve) the expression: 24 ÷ 2^3 - 4 • 5
To simplify the expression using the order of operations, follow these steps:
First, calculate the exponent:
2^3 = 2 x 2 x 2 = 8
Now, let's substitute the values back into the expression:
24 ÷ 8 - 4 • 5
Next, perform the multiplication:
4 • 5 = 20
Now, substitute the new values back into the expression:
24 ÷ 8 - 20
Finally, perform the division:
24 ÷ 8 = 3
Now, substitute the new value back into the expression:
3 - 20
Lastly, perform the subtraction:
3 - 20 = -17
So, the simplified expression is -17.
First, calculate the exponent:
2^3 = 2 x 2 x 2 = 8
Now, let's substitute the values back into the expression:
24 ÷ 8 - 4 • 5
Next, perform the multiplication:
4 • 5 = 20
Now, substitute the new values back into the expression:
24 ÷ 8 - 20
Finally, perform the division:
24 ÷ 8 = 3
Now, substitute the new value back into the expression:
3 - 20
Lastly, perform the subtraction:
3 - 20 = -17
So, the simplified expression is -17.
Evaluate (solve) the algebraic expression below for when y = 4 -3y + 4 (1 point) Responses -8 -8 -1 -1 11 11 16
To evaluate the algebraic expression 4 - 3y + 4 when y = 4, substitute the value of y into the expression:
4 - 3(4) + 4
Now, perform the multiplication first:
4 - 3(4) + 4 = 4 - 12 + 4
Then, perform the addition and subtraction:
4 - 12 + 4 = -8 + 4
Finally, calculate the sum:
-8 + 4 = -4
So, when y = 4, the expression 4 - 3y + 4 evaluates to -4.
4 - 3(4) + 4
Now, perform the multiplication first:
4 - 3(4) + 4 = 4 - 12 + 4
Then, perform the addition and subtraction:
4 - 12 + 4 = -8 + 4
Finally, calculate the sum:
-8 + 4 = -4
So, when y = 4, the expression 4 - 3y + 4 evaluates to -4.
choose one
Evaluate (solve) the algebraic expression below for when y = 4 -3y + 4 (1 point) Responses -8 -8 -1 -1 11 11 16
Evaluate (solve) the algebraic expression below for when y = 4 -3y + 4 (1 point) Responses -8 -8 -1 -1 11 11 16
The correct evaluation of the algebraic expression 4 - 3y + 4 when y = 4 is as follows:
Substitute the value of y into the expression:
4 - 3(4) + 4
Perform the multiplication first:
4 - 3(4) + 4 = 4 - 12 + 4
Then, perform the addition and subtraction:
4 - 12 + 4 = -8 + 4
Finally, calculate the sum:
-8 + 4 = -4
So, when y = 4, the expression 4 - 3y + 4 evaluates to -4.
Substitute the value of y into the expression:
4 - 3(4) + 4
Perform the multiplication first:
4 - 3(4) + 4 = 4 - 12 + 4
Then, perform the addition and subtraction:
4 - 12 + 4 = -8 + 4
Finally, calculate the sum:
-8 + 4 = -4
So, when y = 4, the expression 4 - 3y + 4 evaluates to -4.